An experimental study to see the antihypertensive effects of gymnema sylvestre and acorus calamus in wistar rats and its comparison with amlodipine - Singh, Dheeraj Kumar; Kumar, Narendra; Sachan, Anjula; Lakhani, Preet; Tutu, Sachin; Shankar, Pratap; Nath, Rajendra; Sachan, Amod Kumar; Dixit, Rakesh Kumar (Asian Journal of Medical Sciences, 2017)
Background: The prevalence of obesity is increasing worldwide. Obesity has a direct correlation with insulin resistance and various cardiovascular diseases like hypertension, dyslipidaemia etc. Hypertension is considered as a major independent risk factor for coronary disease and stroke for all age, race & sex groups. Gymnema sylvestre and Acorus calamus are two well known herbs of traditional system of medicine effective in various diseases. Aims and Objectives: The present study was designed to explore the antihypertensive effects of Gymnema sylvestre (GS) and Acorus calamus (AC), individually as well as in combination, in wistar rats. Materials and Methods: Female wistar rats, weighing between 150- 200 g, were included in the study. They were divided into eight groups with six rats in each group. High Fat diet (HFD) was used to induce hypertension in all the groups except group 1 which was fed with normal rodent diet. Drugs were given to the rats by oral feeding cannula. Results: Feeding rats with HFD for 4 weeks lead to signifi cant increase in the mean systolic blood pressure. Both Gymnema sylvestre and Acorus calamus signifi cantly reduced the systolic blood pressure. Combination of both these (Gymnema sylvestre 200mg/kg and Acorus calamus 200mg/kg) as well as Gymnema sylvestre (200mg/kg) individually has an effect comparable to Amlodipine. Individual drugs had no signifi cant effect on heart rate while the combination of these two drugs signifi cantly reduced the heart rate. Conclusions: The present study concludes that extracts of Gymnema sylvestre and Acorus calamus has a signifi cant antihypertensive action in rodent model of hypertension. Combination is found superior to the individual drugs. Asian Journal of Medical Sciences Vol.8(3) 2017 11-15